Neutrophil-lymphocyte ratio as a possible prognostic marker in central nervous system tumors: an integrative literature review (Research, Society and Development, 2022)
Introduction: Gliomas are primary tumors originating in the brain parenchyma. Recent studies explore the role of some leukocytes and other markers of inflammation in clinical outcomes associated with the development and progression of this cancer, among them there is the neutrophil per lymphocyte ratio (NLR). Aim: The purpose of this study is to understand, through studies published in the literature, the quantitative neutrophil/lymphocyte ratio and its implications for the prognosis of patients. Methodology: Integrative literature review on the PubMed database of productions from the last 11 years. The descriptors used were: "glioma", "glioblastoma", "NLR", "neutrophil to lymphocyte ratio", "neutrophil lymphocyte ratio", "neutrophil-to-lymphocyte ratio", "prognostic", "prognosis" and "outcome". Results: Sixteen articles were selected at the end of the search steps. The year 2019 being the most prevalent with 31.25% of the publications, followed by the years 2017 and 2018 appearing each year with 18.75%. Regarding the countries of origin of the studies, 50% were conducted in China, followed by the studies conducted in Turkey with 25%. Therefore, it is assertive that a high NLR rate suggests a worse prognosis in patients with gliomas. This is based on two important considerations: (1) the rate varies according to the grade of the glioma, with high grade gliomas (III and IV) having in most cases higher NLR than low grade gliomas (I and II) and (2) the overall survival of individuals with low NLR is considerably higher than in those with high. Final Considerations: NLR has important value as a low-cost and reliable prognostic biomarker, however, further studies are needed seeking to obtain a common NLR cutoff point.